Trends in health inequalities in 27 European countries - Mackenbach, Johan P; Valverde, José Rubio; Artnik, Barbara; Bopp, Matthias; Brønnum-Hansen, Henrik; Deboosere, Patrick; Kalediene, Ramune; Kovács, Katalin; Leinsalu, Mall; Martikainen, Pekka; Menvielle, Gwenn; Regidor, Enrique; et al. (Proceedings of the National Academy of Sciences - PNAS, 2018)
Unfavorable health trends among the lowly educated have recently been reported from the United States. We analyzed health trends by education in European countries, paying particular attention to the possibility of recent trend interruptions, including interruptions related to the impact of the 2008 financial crisis. We collected and harmonized data on mortality from 1980 to 2014 for 17 countries covering 9.8 million deaths and data on self-reported morbidity from 2002 to 2014 for 27 countries covering 350,000 survey respondents. We used interrupted time-series analyses to study changes over time and country-fixed effects analyses to study the impact of crisis-related economic conditions on health outcomes. Recent trends were more favorable than in previous decades, particularly in Eastern Europe, where mortality started to decline among lowly educated men and where the decline in less-than-good self-assessed health accelerated, resulting in some narrowing of health inequalities. In Western Europe, mortality has continued to decline among the lowly and highly educated, and although the decline of less-than-good self-assessed health slowed in countries severely hit by the financial crisis, this affected lowly and highly educated equally. Crisis-related economic conditions were not associated with widening health inequalities. Our results show that the unfavorable trends observed in the United States are not found in Europe. There has also been no discernible short-term impact of the crisis on health inequalities at the population level. Both findings suggest that European countries have been successful in avoiding an aggravation of health inequalities.